2014
DOI: 10.1159/000366076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Search for Cryptic Sex Chromosomes in Painted Turtles <b><i>Chrysemys picta</i></b>

Abstract: Sex determination is triggered by factors ranging from genotypic (GSD) to environmental (ESD), or both GSD + EE (GSD susceptible to environmental effects), and its evolution remains enigmatic. The presence/absence of sex chromosomes purportedly separates species at the ESD end of the continuum from the rest (GSD and GSD + EE) because the evolutionary dynamics of sex chromosomes and autosomes differ. However, studies suggest that turtles with temperature-dependent sex determination (TSD) are cryptically GSD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 63 publications
1
41
1
Order By: Relevance
“…In addition to the incubation experiments, the 2 preceding studies were unable to detect the sex chromosome in this turtle, leading to the conclusion that it was a TSD species [Nie et al, 2001]. This conclusion was based on the fact that GSD species mainly have a male/female heterogamety genotype with heteromorphic sex chromosomes, while TSD species generally do not [Ezaz et al, 2009b;Valenzuela et al, 2014]. However, the sex chromosome of some GSD reptiles is extremely cryptic to the extent that it may only be detected using high-resolution cytogenetic techniques, such as CGH [Ezaz et al, 2005[Ezaz et al, , 2006Kawai et al, 2007;Martinez et al, 2008;Badenhorst et al, 2013].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to the incubation experiments, the 2 preceding studies were unable to detect the sex chromosome in this turtle, leading to the conclusion that it was a TSD species [Nie et al, 2001]. This conclusion was based on the fact that GSD species mainly have a male/female heterogamety genotype with heteromorphic sex chromosomes, while TSD species generally do not [Ezaz et al, 2009b;Valenzuela et al, 2014]. However, the sex chromosome of some GSD reptiles is extremely cryptic to the extent that it may only be detected using high-resolution cytogenetic techniques, such as CGH [Ezaz et al, 2005[Ezaz et al, , 2006Kawai et al, 2007;Martinez et al, 2008;Badenhorst et al, 2013].…”
Section: Discussionmentioning
confidence: 94%
“…Transitions from TSD to GSD and vice versa are possible along the continuum of sex determination, and some species possess intermediate mechanisms [Sarre et al, 2011;Valenzuela et al, 2003Valenzuela et al, , 2014, even though these types of sex determinations may be evolutionarily unstable [Bull, 1983]. Recent studies have shown the presence of such intermediate sex-determining systems in some reptiles.…”
mentioning
confidence: 99%
“…Cell Culture, Chromosome Preparation, and Chromosome Banding Chromosome preparations were obtained from fibroblast cell cultures established from embryonic or muscle tissue following standard procedures as previously described [Valenzuela, 2009;Badenhorst et al, 2013Badenhorst et al, , 2015Valenzuela et al, 2014;Montiel et al, 2016]. New samples were obtained from private collections or pet trade specimens.…”
Section: Methodsmentioning
confidence: 99%
“…In TSD systems that lack sex chromosomes [Valenzuela et al, 2014] no consistent genotypic difference distinguishes males and females in contrast to sex chromosomal systems. TSD is present in many vertebrates such as crocodilians, tuatara, most turtles, some lizards, and some fish [Valenzuela and Lance, 2004;Tree of Sex Consortium et al, 2014].…”
Section: Vertebrate Sex Determinationmentioning
confidence: 95%
“…At the other extreme of the sex determination spectrum lies environmental sex determination (ESD) where the sexual fate is decided based on environmental factors experienced after fertilization [Bull, 1983;Valenzuela and Lance, 2004]. Temperature is the most common environmental factor that affects sex determination in vertebrates (TSD), where the incubation temperature at a time called the thermosensitive period commits the embryo to the male or female fate [Valenzuela and Lance, 2004;Janzen and Phillips, 2006;Bachtrog et al, 2014] in the absence of sex chromosomes [Valenzuela et al, 2014].…”
mentioning
confidence: 99%